Effects of all-trans retinoic acid on glutamate receptor expression and dendritic spine density in the hypothalamus of rats - Kai, Yuan-Zhong; Xia, Chun; Shan, Qing-Hong; Tang, Zheng-Quan (Frontiers in Neuroscience, 2025)
Increasing evidence suggests that all-trans retinoic acid (ATRA) contributes to the pathogenesis of depression. Although numerous studies have emphasized the role of hippocampal glutamatergic transmission and dendritic spine abnormalities in ATRA-induced depression, it remains unclear whether changes in hypothalamic glutamatergic transmission and dendritic spine density also contribute to its development. This study investigates the effects of ATRA treatment on glutamate receptor expression and dendritic spine density in the hypothalamus of rats. We found that prolonged ATRA exposure induced depression-like behaviors, as evidenced by altered behavior in standard tests. These behavioral changes were accompanied by significant upregulation of retinoic acid receptor α (RARα) and corticotropin-releasing hormone (CRH) expression in the hypothalamus, suggesting a potential involvement of retinoic acid signaling in the regulation of stress-related pathways. Furthermore, rats exhibiting depression-like behaviors after ATRA treatment showed abnormal expression patterns of AMPA receptor subunits. ATRA treatment significantly increases dendritic spine density in hypothalamic neurons, particularly in secondary and tertiary dendrites. Most importantly, significant increases were observed in the GluR1, GluR2, and GluR4 subunits of the AMPA receptor, along with a slight increase in primary dendrite numbers. Additionally, there were significant increases in spine density on secondary and tertiary dendrites, which are critical for synaptic plasticity and neurotransmission. These findings point to a potential disruption in glutamatergic signaling in response to chronic ATRA exposure. In parallel, we observed a significant increase in dendritic spine density in cultured hypothalamic neurons following ATRA treatment. This effect was most pronounced in secondary and tertiary dendrites, indicating a selective enhancement of dendritic complexity. These results suggest that ATRA may alter both synaptic structure and glutamatergic function in the hypothalamus, providing new insights into its potential role in stress-related disorders. Our study highlights the importance of retinoic acid signaling in modulating neural plasticity and provides a novel perspective on the molecular mechanisms underlying ATRA-induced mood disturbances.